Multilevel governance in the temporal protection and integration of Ukrainians within the European Union: the case of Estonia - Jauhiainen Jussi; Erbsen Heidi (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
The war in Ukraine in 2022 resulted in the rapid, large-scale migration of Ukrainians both inside Ukraine and to the European Union (EU). In response, the European Commission and Council activated the 'Temporary Protection Directive' (TPD, 2001) which had been dormant for two decades. This granted Ukrainians fleeing to the EU residence permits, access to the labor market, accommodation, medical care, education for minors, and social and welfare assistance. We analyzed how war-fleeing Ukrainians were received in the EU at three territorial-administrative levels. Through discourse analysis at the supranational (EC and CE), national (Estonian) and subnational (local Estonian) levels and a survey on how 500 temporary protected Ukrainians in Estonia were covered by the TPD, we highlight the hierarchic implementation of the TPD. This case shows the potential and pitfalls of participatory multilevel governance (MLG) for a more sustainable presence and future for the Ukrainian (temporary) diaspora in the EU.